2018
DOI: 10.1016/j.labcli.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del estatus nutricional de vitamina E

Abstract: Estado de revisión: Este documento fue publicado en su primera versión en Documentos de la revista Química Clínica 1996; 15(6): 445-449. La presente versión revisa dicha información, introduce aspectos nutricionales no tratados anteriormente e incorpora un análisis DAFO de la situación actual respecto a la evaluación del estatus de vitamina E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
21

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 30 publications
0
2
0
21
Order By: Relevance
“…While both vitamin A and vitamin C blood levels reflected adequate intakes, it is striking that vitamin E levels were within the normal range despite intake being below recommended values. In this regard, a poor correlation between intake and plasma levels of vitamin E has been reported because vitamin E is mainly transported by lipoproteins, and, therefore, levels of these lipoproteins could determine plasma vitamin E levels [ 51 ]. In this sense, the decrease in plasma vitamin E observed at the end of the study could have been induced by the decreases in lipoprotein (LDL and HDL) levels observed.…”
Section: Discussionmentioning
confidence: 99%
“…While both vitamin A and vitamin C blood levels reflected adequate intakes, it is striking that vitamin E levels were within the normal range despite intake being below recommended values. In this regard, a poor correlation between intake and plasma levels of vitamin E has been reported because vitamin E is mainly transported by lipoproteins, and, therefore, levels of these lipoproteins could determine plasma vitamin E levels [ 51 ]. In this sense, the decrease in plasma vitamin E observed at the end of the study could have been induced by the decreases in lipoprotein (LDL and HDL) levels observed.…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente, la historia se caracteriza por la erradicación en gran medida de enfermedades carenciales, gracias a la administración de las vitaminas sintetizadas y distribuidas comercialmente 48 .…”
Section: Estado Nutricional Bioquímico De Vitaminasunclassified
“…• Vitaminas liposolubles: Se almacenan en el tejido graso e hígado y se absorben más fácilmente en presencia de la grasa alimentaria. Las cuatro vitaminas liposolubles son A, D, E y K. Tienen una estructura basada en la unidad isopreno (figura 1) 48 .…”
Section: Estado Nutricional Bioquímico De Vitaminasunclassified
See 2 more Smart Citations